Innovation and the determinants of firm survival - Hielke Buddelmeyer; Paul H. Jensen; Elizabeth Webster (Institute for the Study of Labor (IZA), 2006)
While many firms compete through the development of new technologies and products, it is well known that new-to-the-world innovation is inherently risky and therefore may increase the probability of firm death. However, many existing studies consistently find a negative association between innovative activity and firm death. We argue that this may occur because authors fail to distinguish between innovation investments and innovation capital. Using an unbalanced panel of over 290,000 Australian companies, we estimate a piecewise-constant exponential hazard rate model to examine the relationship between innovation and survival and find that current innovation investments increase the probability of death while innovation capital lowers it.
urn:nbn:de:101:1-20090406116
Keywords: 330; Innovation; Innovationsmanagement; Risikokapital; Liquidation; Australien